2021
DOI: 10.1515/libri-2021-0054
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions on Cataloging Course

Abstract: Cataloging and metadata description is one of the major competencies that a trainee cataloger must conquer. According to recent research results, library and information studies students experience difficulties understanding the theory, the terminology, and the tools necessary for cataloging. The experimental application of teaching models which derive from predominant learning theories, such as behaviorism, cognitivism, and constructivism, may help in detecting the difficulties of a cataloging course and in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 17 publications
2
7
1
Order By: Relevance
“…As mentioned earlier in this paper, this quantitative survey was based on the CEQ instrument since it is a useful tool to get insights about teaching quality and can help teachers understand the efficiency of the curriculum and how they can improve it (Byrne & Flood, 2003). Additionally, the instrument was expanded with the employment of a self-assessment questionnaire (Kyprianos et al, 2022) allowing the teachers to identify exactly the difficulties of the course taught and how they can address these problems. The CEQ is an instrument developed in Australia where it is extensively used as a performance indicator of teaching quality (Byrne & Flood, 2003).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…As mentioned earlier in this paper, this quantitative survey was based on the CEQ instrument since it is a useful tool to get insights about teaching quality and can help teachers understand the efficiency of the curriculum and how they can improve it (Byrne & Flood, 2003). Additionally, the instrument was expanded with the employment of a self-assessment questionnaire (Kyprianos et al, 2022) allowing the teachers to identify exactly the difficulties of the course taught and how they can address these problems. The CEQ is an instrument developed in Australia where it is extensively used as a performance indicator of teaching quality (Byrne & Flood, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…This section will focus on previous works about the evaluation of cataloguing courses in general with the original RDA, what constitutes an efficient cataloguing course, and what are the core competencies that a future cataloguer should have, since no similar surveys relating to the application of the new official RDA Toolkit into the curriculum have been conducted. When it comes to teaching cataloguing, it appears that several surveys have shown that students prefer more exercises and practical examples than theory (Kyprianos et al, 2022;Chen & Joyce, 2019;Engelson, 2019;Snow & Hoffman, 2015;Al Hijji & Fadlallah;Mugridge, 2008). Moreover, instructor effectiveness is one of the key topics identified in cataloguing course surveys.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations